Desenvolvimento de dispositivos microfluídicos de papel com superfície quimicamente modificada para ensaios clínicos utilizando detecção colorimétrica - Garcia, Paulo de Tarso (2014)
This report describes the development of microfluidic paper-based analytical devices (μPADs) with chemically modified surface for clinical assays with colorimetric detection. The μPADs were fabricated by a stamping-based method with a heated metal stamp for obtain hydrophobic barriers of paraffin in paper. Before of the stamp step, the paper was oxidized to promote the conversion of hydroxyl groups in aldehyde groups for further chemical activation for the immobilization of enzymes. The μPADs were used for complexometric assays of nitrite and bovine serum albumin (BSA) and enzymatic assays of glucose and uric acid (UA). The chemical modification did provide better color uniformity inside of the detection zones of the enzymatic bioassays. After the chemical modification, the relative standard deviation (RSD) values for glucose and UA assays decreased from 40 to 10% and from 20 to 8%, respectively. Clinical assays for glucose, UA, nitrite and BSA were performed in levels which included the clinical range for each bioassay. We performed quantitative analysis of all analytes in artificial urine sample with error values ranged from 2,5 to 4,0%. The robustness tests proved the stability of the chemical modification process and the thermal stability of the μPADs when stored at different temperatures, showing the potential of the devices as trade platforms for clinical analysis. Advantages such as low cost per assay ($ 0.01), portability and easiness of fabrication enable for the use of μPADs in clinical diagnostics in places with limited resources and at the point-of-care, which is the place where the patient requires the analysis.